Impact of Work-Life Balance and Work Engagement on Innovation Work Behavior - Wibowo, Teguh Setiawan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Workers are human resources who function as the most important asset in moving a company so that it can compete or survive with its competitor companies in achieving its goals. To be able to compete or survive this situation, companies need workers who are able to work well and carry out unlimited innovations for the benefit of the company. In the post-Covid-19 era, many companies still implement a work from home system where workers do not need to always go to the office and hold meetings or negotiations with clients via an online system so that work can be completed anytime and anywhere (no restrictions). Without realizing it, this change in work patterns makes the boundaries between personal life and work become blurred, where work is no longer limited by the term